The Wheat Endophyte Epicoccum layuense J4-3 Inhibits Fusarium graminearum and Enhances Plant Growth - Clement Nzabanita; Lihang Zhang; Yanfei Wang; Shuangchao Wang; Lihua Guo (Journal of Fungi, 2023)
Fungal endophytes are well-known for their ability to promote plant growth and hinder fungal diseases, including Fusarium head blight (FHB) caused by Fusarium graminearum. This study aimed to characterize the biocontrol efficacy of strain J4-3 isolated from the stem of symptomless wheat collected from Heilongjiang Province, China. It was identified as Epicoccum layuense using morphological characteristics and phylogenetic analysis of the rDNA internal transcribed spacer (ITS) and beta-tubulin (TUB). In a dual culture assay, strain J4-3 significantly inhibited the mycelial growth of F. graminearum strain PH-1 and other fungal pathogens. In addition, wheat coleoptile tests showed that lesion symptoms caused by F. graminearum were significantly reduced in wheat seedlings treated with hyphal fragment suspensions of strain J4-3 compared to the controls. Under field conditions, applying spore suspensions and culture filtrates of strain J4-3 with conidial suspensions of F. graminearum on wheat spikes resulted in the significant biocontrol efficacy of FHB. In addition, wheat seedlings previously treated with spore suspensions of strain J4-3 before sowing successfully resulted in FHB reduction after the application of conidial suspensions of F. graminearum at anthesis. More importantly, wheat seedlings treated with hyphal fragments and spore suspensions of strain J4-3 showed significant increases in wheat growth compared to the controls under greenhouse and field conditions. Overall, these findings suggest that E. layuense J4-3 could be a promising biocontrol agent (BCA) against F. graminearum, causing FHB and a growth-promoting fungus in wheat.